Komitmen Organisasi dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan Pada PT. Pos Indonesia (Persero) Kantor Cabang Asia Afrika Bandung - Susan; Dewi Yuliati Indah (Jurnal Riset Mahasiswa, 2021)
This study aims to determine the effect of Organizational Commitment and Work Motivation either partially or simultaneously on Job Satisfaction at PT. Pos Indonesia Bandung. This research is a causal associative study using a quantitative approach. The subjects of this study were employees of PT. Pos Indonesia Bandung, totaling 102 employees. The data were collected using questionnaires and interviews, the sampling technique was purposive sampling, while the data analysis was carried out using multiple linear regression analysis. The results showed that the motivation variable was more dominant, because the partial effect on organizational commitment was 29.4% while motivation was 41.4%. Based on the results of the analysis of the coefficient of determination explaining the relationship between motivation and job satisfaction, the result is 41.4% and this shows that partially motivation has a direct effect on job satisfaction and motivation has a greater influence, meaning that PT.Pos employee morale is high.